A Parameterized Mannequin for Apparel Design (Journal of Fiber Bioengineering and Informatics, 2008)
The function of mannequin is important for designing and making clothes, and thegarment size is crucial foundation for making out the standardized mannequins. With the extensiveapplication of the non-contact three-dimensional human body scanning technology, the digitizationof the anthropometric measurement has been realized which provides full support towards computeraided design of mannequins in garment industry. In order to match with the present national standard,intermediate forms of mannequin have been developed for fitting garments made to measure insteadof human body. This paper reports related preliminary research of parameterized mannequin, based onthe survey of female university students in the mid-west area in China. Using statistical calculationsas the foundation, 7 categories of somatotypes were used to obtain intermediate sizes and steppingvalues. This mannequin provides variational control for middle layer measurements with the helpof scanner software. Having measured girths of middle layer across breast, waist and hip separately,change relations after the statistical analysis provide the basis for determining changes in middle layers.Through the programming under the platform of VC++.net and OpenGL, parameterized mannequincan be created, enabling us to construct an intermediate model. Parameterized mannequin can fitstandard series or customized, if necessary, to incorporate changes not only by stepping values basedon statistical analysis, but also by arbitrary adjusting within an allowable range.